Structural Characterization and Immunomodulatory Activity of Polysaccharides from Polygonatum sibiricum Prepared with Deep Eutectic Solvents - Jikun Meng; Chunbo Guan; Qiufeng Chen; Xiao Pang; Heqin Wang; Xinwen Cui; Ran Ye; Xiuqing Zhang (Journal of Food Quality)
Deep eutectic solvents (DES), as a new, efficient, and green solvents, have attracted more attention in recent years. This study was performed to extract Polygonatum sibiricum polysaccharides using DES (DPSP). Subsequently, DPSP was subjected to DEAE-Sepharose Fast Flow and Sephadex G-100 column for further purification (DPSP-3). Structural characterization and immunomodulatory activity in RAW264.7 cells were performed. Results showed that the yield of DPSP was (15.62 ± 0.71)%, and its yield was 1.53 times that of the polysaccharides extracted using the pharmacopoeia method (PSP). DPSP-3 had a smaller molecular weight (3.2 × 106 Da) and a higher ratio of galactose (65.75%) and mannose (19.76%) as compared to PSP. The scanning electron microscope (SEM) showed that DPSP-3 had curly shape, lamellar surface, and a few spherical edges, which were significantly different from PSP and DPSP. Both PSP and DPSP-3 could significantly improve phagotrophic capacity and increase the release of ROS, NO, IL-6, and TNF-α in RAW 264.7 cells, and DPSP-3 had better immunomodulatory activity. In summary, compared to the pharmacopoeia method, polysaccharides prepared using the DES extraction method showed higher yield and improved immunomodulatory activity.